1995
DOI: 10.1227/00006123-199512000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Human Glioma-derived Interleukin-10 Inhibits Antitumor Immune Responses In Vitro

Abstract: Intracranial malignant gliomas are sequestered from the immune system yet are associated with broad suppression of host immunocompetence. Immune system dysfunction in patients with gliomas seems to be related to inhibitory mediators produced by glioma cells. We investigated the physiological roles of glioma-derived interleukin (IL)-10 in Class II expression of monocytes, cytokine secretion from lymphocytes, and T cell proliferation in vitro. We could detect the messenger ribonucleic acid transcript of IL-10 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(46 citation statements)
references
References 27 publications
1
44
0
1
Order By: Relevance
“…In the case of experimental autoimmune encephalomyelitis (EAE), these CD11c+ cells exhibit a maturational phenotype similar to immature BM-derived DC or splenic DCs, and were unable to prime naïve T cells, and in some cases inhibited T-cell proliferation. 1 Gliomas in the brain may also attract and then functionally subvert APC function via tumor-associated factors such as IL-10, TGF-b2 and Fas-L. 2,[34][35][36] Our experiments using adoptively transferred EGFP-DCs demonstrated that few DCs remained within the i.c. tumor lesion by day 5 following Ad-LacZ injection.…”
Section: Glioma Gene Therapy With Ifn-a and Dcsmentioning
confidence: 99%
“…In the case of experimental autoimmune encephalomyelitis (EAE), these CD11c+ cells exhibit a maturational phenotype similar to immature BM-derived DC or splenic DCs, and were unable to prime naïve T cells, and in some cases inhibited T-cell proliferation. 1 Gliomas in the brain may also attract and then functionally subvert APC function via tumor-associated factors such as IL-10, TGF-b2 and Fas-L. 2,[34][35][36] Our experiments using adoptively transferred EGFP-DCs demonstrated that few DCs remained within the i.c. tumor lesion by day 5 following Ad-LacZ injection.…”
Section: Glioma Gene Therapy With Ifn-a and Dcsmentioning
confidence: 99%
“…IL-10 liberated by gliomas has also been shown to reduce the antigen presenting capacity of monocytes by down modulating MHC Class II expression, thus hindering antigen stimulated proliferation of T cells. 39 IL-10 mediated suppression of human T cell proliferation could be overcome with exogenous IL-2. 29 Our observation also showed that with exogenous IL-2 application in glioma-induced conditions, significant increase (p < 0.001) in the PTK activity was observed in cytosolic and membrane fraction of lymphocytes and in the membrane fraction of microglia membrane.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Secretion of interleukin 10 (IL-10), a Th2 type cytokine, correlates with a poor prognosis for human astrocytic tumors. 46 IL-10 downregulates expression of MHC class II determinants by monocytes and inhibits IFN-g and TNF-a production. 47,48 It also drives immune responses toward the Th2 pathway and prevents stimulation of Th1 type immune responses needed for activation of cytolytic T cells.…”
Section: Discussionmentioning
confidence: 99%